Automation in Information Technology: Implication on Job Market In India (International Journal of Engineering and Computer Science, 2018)
The world is growing very fast from recent decades. This growth is strongly assisted by technological advancements. From the past few years the technology has taken various forms to aid the people and the companies. Both companies and the people are getting mammoth benefits out of these technological advancements. The changes in technology have created numerous jobs all over the world. And the companies are expecting to create more millions of jobs in the coming future. The technology has made the life easy and comfortable. The companies are investing huge money on research and development. Result of this research and development is automation, which is a latest trend in Information Technology sector. Slowly this has taken more sophisticated form of technology. The development is paced up with this automation. The automation is fast absorbed by IT Companies. The IT companies are deploying automation technologies all over the world in order to reduce maintenance and labour costs. My study tries to focus on the concept of automation in IT, forms of automation and its implication on job market in Indian Information Technology sector.